Elucidating the Influence of TikTok Gratification on Psychological Well-Being and Life Satisfaction among Young Muslim Users - Hassan, Siti Hasnah; Eve Chee, Low; Mat Saad , Norizan; Al-Kumaim, Nabil Hasan (International Review of Management and Marketing, 2025)
TikTok usage trends are continually evolving, and young Muslims’ experiences and preferences on the platform may vary across different countries, cultures, and individual contexts. This study examines the impact of TikTok gratification on the psychological well-being and life satisfaction of Malaysian Muslims aged 18-24. Utilizing survey methods and purposive snowballing, data from 350 participants were analyzed via SmartPLS 4.0. The findings indicate that socially rewarding self-presentation, trendiness, and escapist addiction significantly influenced self-gratification, positively contributing to psychological well-being and life satisfaction within this demographic. The research highlights TikTok's potential for young Muslims to express creativity, embrace cultural identity, and promote positive Islamic representations. These insights are valuable for policymakers, psychologists, NGOs, educators, and content creators seeking to enhance the well-being and empowerment of young Muslim users in the digital era. This study offers new insights into TikTok gratification and its effects on psychological well-being and life satisfaction in the Muslim-majority nations.